2014
DOI: 10.1093/bja/aeu090
|View full text |Cite
|
Sign up to set email alerts
|

Morphine stimulates cancer progression and mast cell activation and impairs survival in transgenic mice with breast cancer

Abstract: Morphine does not affect the onset of tumour development, but it promotes growth of existing tumours, and reduces overall survival in mice. MOR may be associated with morphine-induced cancer progression, resulting in shorter survival. Mast cell activation by morphine may contribute to increased cytokine and SP levels, leading to cancer progression and refractory pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(139 citation statements)
references
References 39 publications
4
130
1
4
Order By: Relevance
“…26) However, other studies found that morphine might increase tumor progression and promote tumor angiogenesis, cancer cell invasion and metastasis in vivo. [27][28][29] Morphine promotes breast cancer stem cell properties and tumor growth via activating Wnt/β-catenin signaling. 30) Naloxone reversed the inhibition on tumor cell adhesion of morphine, but did not influence the inhibitory effect on the production of matrix metalloproteinases (MMPs) from tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…26) However, other studies found that morphine might increase tumor progression and promote tumor angiogenesis, cancer cell invasion and metastasis in vivo. [27][28][29] Morphine promotes breast cancer stem cell properties and tumor growth via activating Wnt/β-catenin signaling. 30) Naloxone reversed the inhibition on tumor cell adhesion of morphine, but did not influence the inhibitory effect on the production of matrix metalloproteinases (MMPs) from tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…53 Morphine does not influence the initiation of tumour development; rather, it affects the progression of established breast tumour, as recently shown in a transgenic mouse study that found significantly decreased survival in a mouse model of breast adenocarcinoma. 54 In the same study, it was found that morphine promoted lymphangiogenesis, mast cell activation and degranulation, and increased levels of inflammatory cytokines, tryptase, and substance P. In addition, the morphine-treated mice had increased tumour burden and decreased duration of survival. 54 In an immunohistochemical study on the effect of MOR on metastasis, patients who had excision of non-small cell lung carcinoma were evaluated for their MOR status.…”
Section: Opioidsmentioning
confidence: 94%
“…54 In the same study, it was found that morphine promoted lymphangiogenesis, mast cell activation and degranulation, and increased levels of inflammatory cytokines, tryptase, and substance P. In addition, the morphine-treated mice had increased tumour burden and decreased duration of survival. 54 In an immunohistochemical study on the effect of MOR on metastasis, patients who had excision of non-small cell lung carcinoma were evaluated for their MOR status. There was a direct correlation between MOR expression and the extent of metastasis in these patients.…”
Section: Opioidsmentioning
confidence: 94%
“…Pro-angiogenic activity of opioids was shown in studies where morphine enhanced endothelial cell proliferation [22,65] and tube formation in vitro, and angiogenesis in vivo in the matrigel plug assay and in breast tumor xenografts [22]. This was confirmed using a syngeneic [66] and an endogenous [67] mouse breast tumor model. Potential mechanisms for angiogenesis promotion include increased COX2 activity [66] and transactivation of vascular endothelial growth factor (VEGF) receptor by opioids [68].…”
Section: Indirect Effects Of Opioids On Tumor Biologymentioning
confidence: 78%